THE EMPIRICAL STUDY OF INTEREST RATE VOLATILITY IN TAIWAN BOND MARKET - Chen, Yu-Ching (2009)
Interest rate is one of the most important factors to affect the financial market. Almost all kinds of assets which can be invested have the relationship with interest rate.